PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TEKNIK KEPALA BERNOMOR UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IX7 SMP NEGERI 8 PEKANBARU - Oktayani Putri Putri; Zulkarnain '; Yenita Roza Roza (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research based on the student’s mathematics achievement in class IX7 of SMPN 8 Pekanbaru, there are 12 of 32 students who achieved the Minimum Mastery Criteria or 37,5% for similarity lesson. This research aims to improve the learning process and increase the student’s mathematics achievement by applying the model of Cooperative Learning Numbered Head Techniques. The subject of this research were the students in class IX7 SMPN 8 Pekanbaru, there are 32 students with heterogeneous level of academic capabilities. This research is a class action research by two cycles. The instruments of data collection in this research were observation sheets and students mathematic tests. The observation sheets were analyzed in qualitative, while the student’s mathematic tests were analyzed in quantitative. The qualitative descriptive showed that there is the improvement of learning process after the action on the first and second cycles. The result showed that there is an increase in student’s achievement from the basic score with the percentage 37,5% to 56,25% on the first test and 78,1% on the second test. Based on the result of this research, can be concluded that the implementation of Cooperative Learning Numbered Head Techniques can improve the learning process and increase the student’s mathematics achievement class IX7 of SMPN 8 Pekanbaru by the academic years 2014/2015. Key Words: Student’s Mathematics Achievement, Cooperative Learning Numbered Head Techniques, Class Action Research.